1999
DOI: 10.1359/jbmr.1999.14.6.969
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bisphosphonate (Incadronate) on Fracture Healing of Long Bones in Rats

Abstract: This study was designed to test whether bisphosphonates disturb the process of fracture healing. Female SpragueDawley rats were injected with either two doses of bisphosphonate (incadronate) (10 µg/kg and 100 µg/kg) or vehicle three times a week for 2 weeks. Right femora were then fractured and fixed with intramedullary wires. Incadronate treatment was stopped in pretreatment groups (P-10 and P-100 groups), while the treatment was continued in continuous treatment groups (C-10 and C-100 groups). Animals were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
133
4
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(158 citation statements)
references
References 49 publications
15
133
4
6
Order By: Relevance
“…In complete fractures in rats, bisphosphonate treatment does not alter the rate of bone union and consistently results in a larger callus. 12,13,36 Similar results were observed in models using dogs and sheep. 37,38 In these studies, mechanical properties of the callus were improved 3,12,13,36 or not significantly changed by treatment with bisphosphonates.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In complete fractures in rats, bisphosphonate treatment does not alter the rate of bone union and consistently results in a larger callus. 12,13,36 Similar results were observed in models using dogs and sheep. 37,38 In these studies, mechanical properties of the callus were improved 3,12,13,36 or not significantly changed by treatment with bisphosphonates.…”
Section: Discussionsupporting
confidence: 79%
“…In experimental studies of complete fracture in rats, treatment with bisphosphonates consistently increased the hard callus volume, strength and mineral content. 3,12,13 In animal models, stress fractures heal by direct remodeling along the fracture line. 14,15 Treatment with bisphosphonates may therefore have a negative effect on stress fracture healing when compared to complete fractures.…”
mentioning
confidence: 99%
“…As observed with bisphosphonate therapy, withdrawal of the agent restores osteoclast numbers and activity during the remodeling phase of fracture healing [24,25,29]. We also found that RANK signaling is not required for the early phase of fracture healing as evidenced by the repair (callus formation) observed in RANK 4-mice.…”
Section: Discussionsupporting
confidence: 70%
“…The drug at too high concentrations could then have detrimental effects on the fixation of the implant over longer periods of time. Indeed, conflicting studies have reported that the use of bisphosphonate can interact with the repair of cracks and fractures, while other studies were unable to demonstrate this phenomena [17,[21][22][23]. Specifically for the zoledronate, it has been shown that aminobisphosphonate (like zoledronate), due to the lower dosing, will not impair with the fractures and cracks repair [4].…”
Section: Discussionmentioning
confidence: 99%